Talent Management Through Lecturers Competency Evaluation Rubic in Study Programs in Higher Education - ., Iswan; Murod, Ma’mun; ., Herwina; Sundi, Veni Herli (International Journal of Membrane Science and Technology, 2023)
Research with the title: Talent Management Through Lecturers Competency Evaluation Rubric in Study Programs Higher Education, where this research was conducted at the Faculty of Education, Universitas Muhammadiyah Jakarta, Indonesia in the odd semester of the 2021/2022 academic year with the distribution of competencies for AIK courses, which are spread across various programs studies in FIP-UMJ, including PGPAUD, PGSD, PENDMAT, PBI, PBSI, POR, PTI. MTP. The number of respondents studied amounted to 27 lecturers, especially those who teach courses according to their competence. The research method with a qualitative descriptive approach. The results of this study indicate that based on the findings in this study there are still 0.11% who are irrelevant to the competency area, but based on the data obtained the person concerned has a background that supports the AIK learning process, especially at the Universitas Muhammadiyah Jakarta, Indonesia. There were three research objectives led the authors to conduct this study, namely: 1) to present the elements used in lecturers’ competencies evaluation rubric; 2) to analysis each of the element assessed in the rubric according to educational system and practice; 3) to report the extent in which this evaluation aligns with talent management practice. The findings revealed that first, the elements used in the rubric needs to be re-evaluated in terms of the statements presented in the questionnaire and the scale; second, each of the element in the rubric is suitable with the qualities mandated by Indonesian Acts for teachers and lecturers No. 14/2005 and proven to be effective by prior studies; third, this evaluation rubric is said to be align with the implementation of talent management in which competencies of the lecturers will obviously support the institution to compete with other private universities and reach its vision, missions, and objectives.